(untitled) - Collier, Simon (New York, 2003)
Simon Collier examines the formative period of the Chilean republic's history. He combines an analysis of the ideas and assumptions of the Chilean political class with a narrative of the political process from the consolidation of the Conservative regime in the 1830s, to the beginning of the liberalization in the early 1860s. Chile's stable and increasingly liberal political tradition was forged in serious and occasionally violent conflicts between the dominant Conservative Party (which governed in an often authoritarian manner from 1830 to 1858) and the growing forces of political Liberalism. A major political realignment in 1857-8 paved the way for comprehensive liberalization
Keywords: Chi lê; Chính trị và chính phủ; 1824-1920